New Strategy of Synthesis of Peramivir Analogues as Potential Neuraminidase Inhibitors - Bartolotta, Roberta; La Rosa, Concetta; Nava, Donatella (Synthesis, 2020)
Highly functionalised potential neuraminidase (NA) inhibitors, analogues of peramivir, were synthesised via a new and versatile method starting from a stereoselective 1,3-dipolar cycloaddition reaction between the nitrile oxide derived from 2-ethylbutanal and the commercially available and inexpensive cyclopentadiene and 1,3-cyclohexadiene, which afforded the isoxazolino-cyclopentene or cyclohexene intermediates, respectively. The subsequent reaction of the C=C bond in different conditions allowed the functionalisation of the five (or six) membered carbon nucleus. Further functionalised derivatives displaying an amino and a hydroxyl group were achieved via the final opening of the isoxazoline ring.
Keywords: peramivir; neuraminidase inhibitors; 1,3-dipolar cycloaddition; isoxazolines; cyclopentadiene; 1,3-cyclohexadiene